THE HISTORY OF RAILWAY TERMS (World Bulletin of Management and Law, 2025)
Railway terminology has played a crucial role in shaping the technical and cultural lexicon of transportation. This article explores the historical development of railway terms, tracing their origins, evolution, and significance in global contexts. By examining the linguistic influences, technological advancements, and societal impacts, this study offers insights into how railway terminology reflects broader historical trends and contributes to the field of transportation linguistics